BRIDGING ARITHMETIC TO ALGEBRA: IMPLEMENTING AN E-MODUL THROUGH DIDACTICAL DESIGN RESEARCH - Lia Ardiansari; Dyah Ariyanti; Mohammad Sahrul Rozi; Muhammad Fajar Assiddiqi (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Students' difficulties in understanding algebraic concepts often stem from a procedural approach to arithmetic without deep conceptual grounding. This study aims to develop and implement an interactive e-module titled “Jembatan Aritmatikaâ€, designed to help students build a conceptual transition from arithmetic to algebra by deepening their understanding of the equal sign (=) as a relational symbol. The study adopts a Didactical Design Research (DDR) approach, consisting of three main phases: preliminary design, experimental teaching, and retrospective analysis. The participants were upper-grade elementary school students who engaged with the e-module across several learning sessions. Instruments included pre-test and post-test questions, observation sheets, and student response questionnaires. The results showed that the e-module effectively enhanced students' understanding of the relational meaning of the equal sign and introduced them to the fundamental structure of algebraic equations in a gradual and meaningful way. Strategies such as visualization, contextual problem-solving, and the progressive use of symbolic representation proved helpful in supporting students’ reasoning about quantitative relationships. The study concludes that the “Jembatan Aritmatikaâ€ e-module holds promise as an effective learning medium for facilitating students' conceptual transition from arithmetic to algebra.